Critical Thinking in Da'wah: Bridging Text and Context - Rais Harahap, Amin; Mailin, Mailin (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2025)
This study aims to analyze the urgency and implementation of critical thinking in modern Islamic preaching as a bridge between text and context. The research method used is library research by examining relevant scientific sources in the form of national and international journal articles, academic books, and empirical research results. Data analysis was carried out thematically through a content analysis approach and supported by bibliometric visualization using VOSviewer for 150 related articles. The results of the study show that critical thinking is the main pillar in developing adaptive contextual preaching in the digital era. Bibliometric visualization shows that critical thinking is the main node that is closely connected to the theme of digital preaching, religious moderation, and prevention of radicalism. The implementation of critical thinking in preaching includes evaluative abilities towards sources of teachings, contextual awareness of the audience, dialogical openness, and ethical reflection in responding to differences. The strategy for strengthening implementation includes reformulating the dai education curriculum, digital media literacy training, and developing interactive discussion forums based on scientific arguments. This study emphasizes that strengthening critical attitudes in da'wah is an epistemological need to produce moderate, solution-oriented da'wah messages that are relevant to the dynamics of the times.